Movement patterns of lesser flamingos Phoeniconaias minor: nomadism or partial migration?. Issue 3 (19th August 2020) - Pretorius, Mattheuns D.; Leeuwner, Lourens; Tate, Gareth J.; Botha, André; Michael, Michael D.; Durgapersad, Kaajial; Chetty, Kishaylin
Abstract : Waterbirds in stochastic environments exhibit nomadism in order to cater for the unpredictable availability of water resources. Lesser flamingos Phoeniconaias minor have long been thought to be nomadic waterbirds. In southern Africa, conservation efforts for lesser flamingos are hampered by a lack of knowledge about their movement trajectories. To investigate their movement ecology in southern Africa, we fitted GPS–GSM transmitters to 12 adults and tracked their movements over four years, from March 2016 to February 2020. Net squared displacement (NSD) was used in nonlinear least squares models classifying trajectories as nomadic, migratory, mixed‐migratory, home range restricted or dispersal movement types. Data from eight of the 12 birds met the criteria for the NSD analysis. Model success was good; only 8 out of 120 (6.7%) movement type models failed to reach convergence. Goodness of fit statistics from the NSD models supported migratory and mixed migratory movement types (concordance criteria coefficient (CC) = 0.78) for more than half of the annual trajectories investigated (57.2%). Dispersal, home range‐restricted and nomadic movements best described 28.6, 9.5 and 4.8% of annual trajectories, respectively, but all resulted in a mean CC of < 0.4 and thus did not fit observed NSD patterns as well as the migratory movement types. We then used nonlinear mixed effects models to account for annual and individual differences in migration parameters. Variation in the timing and duration of all migrations were more important than variation in migration distance, indicating well‐established summer and winter 'ranges' and routes between Kamfers Dam (South Africa) and Sua Pan (Botswana). We propose that lesser flamingos in central southern Africa may be partial migrants, not true nomads, as most of their movements followed a regular, repeated pattern between two primary locations.